2015
DOI: 10.1038/ncomms7060
|View full text |Cite
|
Sign up to set email alerts
|

Origins of hydration lubrication

Abstract: Why is friction in healthy hips and knees so low? Hydration lubrication, according to which hydration shells surrounding charges act as lubricating elements in boundary layers (including those coating cartilage in joints), has been invoked to account for the extremely low sliding friction between surfaces in aqueous media, but not well understood. Here we report the direct determination of energy dissipation within such sheared hydration shells. By trapping hydrated ions in a 0.4-1 nm gap between atomically sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
292
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(324 citation statements)
references
References 30 publications
18
292
0
1
Order By: Relevance
“…[ 28 ] Second, shearing off whole adsorbed mucin macromolecules from either the PDMS or the steel surface may additionally contribute to the observed reduction in friction. [ 24 ] When coatings were built from partially or fully deglycosylated mucins, the friction coeffi cient was as high as without any mucin coating.…”
Section: Mucin Deglycosylation Results In Dehydrated and Poorly Lubrimentioning
confidence: 99%
“…[ 28 ] Second, shearing off whole adsorbed mucin macromolecules from either the PDMS or the steel surface may additionally contribute to the observed reduction in friction. [ 24 ] When coatings were built from partially or fully deglycosylated mucins, the friction coeffi cient was as high as without any mucin coating.…”
Section: Mucin Deglycosylation Results In Dehydrated and Poorly Lubrimentioning
confidence: 99%
“…We confirm the existence of highly conductive magnetic DWs by direct imaging with microwave impedance microscopy (MIM). MIM is a scanning probe technique that probes local conductivity by measuring tip-sample impedance at ~1 GHz (20)(21)(22): more conductive regions screen the microwave electric field better, resulting in a smaller tip-sample impedance. Working at high frequency eliminates the need of a back electrode and a complete current path, making MIM ideal for bulk insulating samples (23).…”
mentioning
confidence: 99%
“…This allowed the clear observation of different dissipation regimes, and enabled the isolation of frictional dissipation arising from the shear of the sub-nanometer hydration shells themselves, intrinsic to all hydration lubrication processes, from any system-dependent dissipation mechanisms, as shown in Fig. 5 [24]. The experiment suggested that frictional forces even in such simple systems can be dominated by rate-activated pathways.…”
Section: Liquid Superlubricitymentioning
confidence: 88%